A TNFR2-Specific TNF Fusion Protein With Improved In Vivo Activity - Vargas, Juan Gamboa; Wagner, Jennifer; Shaikh, Haroon; Lang, Isabell; Medler, Juliane; Anany, Mohamed; Steinfatt, Tim; Mosca, Josefina Peña; Haack, Stephanie; Dahlhoff, Julia; Büttner-Herold, Maike; Graf, Carolin; et al. (Frontiers in Immunology, 2022)
Tumor necrosis factor (TNF) receptor-2 (TNFR2) has attracted considerable interest as a target for immunotherapy. Indeed, using oligomeric fusion proteins of single chain-encoded TNFR2-specific TNF mutants (scTNF80), expansion of regulatory T cells and therapeutic activity could be demonstrated in various autoinflammatory diseases, including graft-versus-host disease (GvHD), experimental autoimmune encephalomyelitis (EAE) and collagen-induced arthritis (CIA). With the aim to improve the in vivo availability of TNFR2-specific TNF fusion proteins, we used here the neonatal Fc receptor (FcRn)-interacting IgG1 molecule as an oligomerizing building block and generated a new TNFR2 agonist with improved serum retention and superior in vivo activity. Methods: Single-chain encoded murine TNF80 trimers (sc(mu)TNF80) were fused to the C-terminus of an in mice irrelevant IgG1 molecule carrying the N297A mutation which avoids/minimizes interaction with Fcg-receptors (FcgRs). The fusion protein obtained (irrIgG1(N297A)-sc(mu)TNF80), termed NewSTAR2 (New selective TNF-based agonist of TNF receptor 2), was analyzed with respect to activity, productivity, serum retention and in vitro and in vivo activity. STAR2 (TNC-sc(mu)TNF80 or selective TNF-based agonist of TNF receptor 2), a well-established highly active nonameric TNFR2-specific variant, served as benchmark. NewSTAR2 was assessed in various in vitro and in vivo systems. Results: STAR2 (TNC-sc(mu)TNF80) and NewSTAR2 (irrIgG1(N297A)-sc(mu)TNF80) revealed comparable in vitro activity. The novel domain architecture of NewSTAR2 significantly improved serum retention compared to STAR2, which correlated with efficient binding to FcRn. A single injection of NewSTAR2 enhanced regulatory T cell (Treg) suppressive activity and increased Treg numbers by > 300 % in vivo 5 days after treatment. Treg numbers remained as high as 200 % for about 10 days. Furthermore, single NewSTAR2 in vivo treatment upregulated the adenosine-regulating ectoenzyme CD39 and other activation markers on Tregs. TNFR2-stimulated Tregs proved to be more suppressive than unstimulated Tregs, reducing conventional T cell (Tcon) proliferation and expression of activation markers in vitro. Finally, singular preemptive NewSTAR2 administration five days before allogeneic hematopoietic cell transplantation (allo-HCT) protected mice from acute GvHD. Conclusions: NewSTAR2 represents a next generation ligand-based TNFR2 agonist, which is efficiently produced, exhibits improved pharmacokinetic properties and high serum retention with superior in vivo activity exerting powerful protective effects against acute GvHD.